Advanced Aerogels for Water Remediation: Unraveling Their Potential in Fats, Oils, and Grease Sorption—A Comprehensive Review - Adina-Elena Segneanu; Dumitru-Daniel Herea; Gabriela Buema; Ionela Amalia Bradu; Melinda Cepan; Ioan Grozescu (Gels)
The increasing contamination of water bodies by fats, oils, and grease (FOG) poses significant environmental and operational challenges, necessitating the development of advanced remediation technologies. Aerogels, with their ultra-lightweight structure, high porosity, and tunable surface chemistry, have emerged as promising sorbents for efficient FOG removal. This comprehensive review explores recent advancements in aerogel materials, highlighting novel formulations, functional modifications, and nanotechnology integrations that enhance sorption capacity and reusability. It delves into the mechanistic aspects of FOG sorption, providing insights into how surface interactions and structural properties influence performance. The sustainability of aerogels is emphasized, particularly the use of bio-based and eco-friendly materials that align with green remediation strategies. A comparative analysis with conventional sorbents underscores the advantages of aerogels in terms of efficiency, environmental impact, and cost-effectiveness. Furthermore, real-world applications, including oil spill cleanup and wastewater treatment, are discussed alongside challenges, regulatory considerations, and future research directions. By offering a holistic perspective on the potential of aerogels in water remediation, this review serves as a valuable resource for researchers and industry professionals seeking innovative and sustainable solutions for FOG management.